2012
DOI: 10.1134/s1063780x12010096
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen lines in the infrared region and spectral background for the thomson scattering diagnostics of the iter divertor plasma

Abstract: Calculations are made of the plasma spectral background, which is important for the Thomson scattering diagnostics in the ITER divertor. Theoretical grounds have been elaborated for computing the hydrogen spectral line shapes in the infrared spectral region for a divertor plasma in ITER. The shape of the P 7 Paschen line (transition n = 7 n = 3) located near the laser scattering signal has been calculated for various lines of sight in the ITER divertor. Contributions from different mechanisms of broadening the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Such an approach saving the dynamic range of detectors cannot remove shot noise, which is proportional to the square root of the signal intensity and reduces the accuracy of the T e and n e measurements. According to intensity of the background radiation in the DTS working spectral range 1-1.06 µm analysed previously [1,14,15], blackbody radiation resulting from the intense plasma heating of the divertor targets and line radiation appearing in nitrogen seeded plasma can be the limiting background comp onents. Nitrogen, injected into the divertor region to provide the radiative dissipation necessary to achieve plasma detachment, has a spectral line at ~1.011 µm with intensity ~10 times higher than the expected TS signal integrated over a 15 nm spectral interval.…”
Section: Dts-technical Requirements and Approachesmentioning
confidence: 99%
“…Such an approach saving the dynamic range of detectors cannot remove shot noise, which is proportional to the square root of the signal intensity and reduces the accuracy of the T e and n e measurements. According to intensity of the background radiation in the DTS working spectral range 1-1.06 µm analysed previously [1,14,15], blackbody radiation resulting from the intense plasma heating of the divertor targets and line radiation appearing in nitrogen seeded plasma can be the limiting background comp onents. Nitrogen, injected into the divertor region to provide the radiative dissipation necessary to achieve plasma detachment, has a spectral line at ~1.011 µm with intensity ~10 times higher than the expected TS signal integrated over a 15 nm spectral interval.…”
Section: Dts-technical Requirements and Approachesmentioning
confidence: 99%
“…Experimental studies carried out in the near-infrared (NIR) region show that the strongest spectral lines in the DTS operational range are the hydrogen line of the Paschen series with wavelength ∼1.005 µm (P-7) and the nitrogen line at ∼1.011 µm. The ITER divertor background radiation intensity collected along DTS probing chords has been evaluated previously [9] accounting for the continuous spectrum of Bremsstrahlung, recombination radiation, and the P-7 line radiation intensity. It was concluded that these contributions have nearly the same order of magnitude and are 1-2 orders of magnitude lower than TS signal.…”
Section: Background Radiationmentioning
confidence: 99%
“…[13][14][15] The components of the emissions, e.g., the blackbody, bremsstrahlung, recombination, and impurity lines, including C, N, O, Ne, and P7 lines, can significantly contribute to the system noise, hence a validated background emission model for diagnostic performance assurance is needed. The P7 line at λ = 1049 nm is of particular concern, as it falls within the range actively used for T e ≤ 100 eV measurements.…”
Section: B Emission In the Range 1-106 μM For Thomson Scattering DImentioning
confidence: 99%